Effectiveness of the Application of Internal Control Structure, Capital and Management Knowledge about Cooperative Accounting (SAK ETAP) toward Cooperative Performance - Evi Yuniarti (Jurnal Ilmiah ESAI, 2014)
The purpose of this study is to analyze the effect of internal control structure effectiveness, capital, and management knowledge about cooperative accounting (SAK ETAP) simultaneously and partially to the cooperative performance. This research used explanatory survey method and were analized by descriptive and verification test. The data was collected by distributing questionare as primary data and collecting financial statement as secondary. The path analysis model was used to measure the impact of exogenous variables on endogenous variables directly and indirectly. Based on this research, it was found that 1) simultaneously hypothesis testing showed the internal control structure effectiveness, capital, and management knowledge about cooperative accounting (SAK ETAP) influence to the cooperative performance.2) partialy amount of the total effect of the internal control structure to the cooperative performance was 22.84%, with positive direction. While the magnitude of the total effect of knowledge management on cooperatives accounting (SAK ETAP) to the cooperative performance was 42.74% with a positive direction.Key words: internal control effectiveness, capital, cooperative accounting, cooperative performance